ANALISIS PENGARUH WORK FAMILY CONFLICT, BURNOUT DAN DUKUNGAN SOSIAL TERHADAP KINERJA KARYAWAN WANITA (STUDI KASUS PADA PT. CHIA JIANN INDONESIA FURNITURE) - Frenda Yunani, Indria; Violinda, Qristin; Shobaruddin Akbar, Shofif (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2024)
This study aims to analyze the influence of work-family conflict, burnout, and social support on employee performance at PT Chia Jiann Furniture Indonesia. These three factors are considered important in determining how well employees can function in their jobs, with work-family conflict and burnout being able to decrease performance, while social support can increase performance. The population and sample used are the same because the number of employees is not too many, namely 150 using a saturated sampling technique. Quantitative research methods were used with data collection through questionnaires completed by 150 female employees. Data analysis was conducted using simple linear regression to determine the relationship between the variables studied. The results showed that work-family conflict has a positive and significant effect on employee performance. Burnout also has a positive and significant effect on performance. Social support has a positive and significant effect on employee performance. This study confirms that work-family conflict and burnout have a significant negative impact on employee performance, while social support has a significant positive impact. It is important for companies to manage work-family conflict and reduce burnout, while strengthening social support to improve employee performance.